Risk Analysis and Innovative Product Management in Rosatom State Corporation: A Case Study of a Green Project Floating Nuclear Thermal Power Plant “Akademik Lomonosov” - Marina A. Allenykh; Alina I. Anisimova (Review of Business and Economics Studies, 2023)
Risk management plays a crucial role in ensuring the dynamic development and energy security of the national economy in the nuclear sector. This study focuses on the application of the smart card method for evaluating risks in the energy sector, using the example of a carbon-free energy technology development project at Rosatom State Corporation. The subject of the research is the Floating nuclear thermal power plant "Akademik Lomonosov", which is designed to provide reliable electricity and heat supply to consumers in the Far North and Far East regions. This project is one of the key directions for developing the new business block in the State Corporation Rosatom. The aim of this study is to evaluate the risk management of innovative projects in the green nuclear sector, with a focus on the Floating nuclear thermal power plant "Akademik Lomonosov". The authors used the methods of comparative analysis, system analysis, the analysis of statistical data, financial reports, and official documents. The results show that risk management is crucial for ensuring the dynamic innovative development of nuclear energy in the near-, medium- and long-term, and the smart card can be a beneficial tool in this regard. The key conclusion of the study is that the green project Floating nuclear thermal power plant "Akademik Lomonosov" has been successfully prepared for operation, considering most of the key risks. The risk evaluation conducted using the smart card method has demonstrated its effectiveness in identifying and managing risks associated with the project. The authors emphasize the importance of integrating smart cards into risk assessment practices in the nuclear industry and highlight their potential for use in future projects.